Review on Decentralized Application Using Block Chain - Srivastava, Anukool; Verma, Shubham (International Journal of Psychosocial Rehabilitation, 2024)
Elections are the prime attribute in the fate of a country. Current Election Systems are a Client Server Model based on a Centralized Database. The problem resides with a Central Authority where data could be changed or manipulated by the administrator without the knowledge of other. The survey proposed is on decentralized systems implemented using Ethereum Blockchain which enables full distribution of data along with security. A comparison between centralized and decentralized systems are used to draw out the advantage of using Blockchain as the distributed system. Migrating the code and data on a blockchain ensures the proper security of the system and any changes that need to be done in it should require a Transaction which will be reflected to each node connected to the blockchain.